2008
DOI: 10.1016/j.cmet.2008.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Cavin/PTRF Causes Global Loss of Caveolae, Dyslipidemia, and Glucose Intolerance

Abstract: SUMMARY Caveolae are specialized invaginations of the plasma membrane found in numerous cell types. They have been implicated as playing a role in a variety of physiological processes and are typically characterized by their association with the caveolin family of proteins. We show here by means of targeted gene disruption in mice, that a distinct caveolae-associated protein, Cavin/PTRF, is an essential component of caveolae. Animals lacking Cavin have no morphologically detectable caveolae in any cell type ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
339
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(364 citation statements)
references
References 47 publications
22
339
0
1
Order By: Relevance
“…As a final step in quantitatively characterizing Cav1 dynamics, we down-regulated cavin1, a crucial regulator of caveolar formation (16,33). As confirmed in Fig.…”
Section: Diffusional Analysis Of Cav1-gfp Features In Untreated Cellsmentioning
confidence: 73%
“…As a final step in quantitatively characterizing Cav1 dynamics, we down-regulated cavin1, a crucial regulator of caveolar formation (16,33). As confirmed in Fig.…”
Section: Diffusional Analysis Of Cav1-gfp Features In Untreated Cellsmentioning
confidence: 73%
“…After caveolins have trafficked to the plasma membrane, multimeric cavin complexes in the cytosol are recruited to the cytoplasmic surface of caveolae, where they stabilize caveolins (22,36). Among the cavins, cavin 1 is most critical for stabilization of caveolins and caveolae biogenesis (25,26,37). We therefore hypothesized that ablation of Fgf13 affected the relative distribution of cavin 1 and led to stabilization of caveolae.…”
Section: Fgf13 Regulates the Distribution Of Cavin 1 Between The Plasmamentioning
confidence: 99%
“…The functions of caveolins are closely linked to a family of cytoplasmic proteins termed cavins (Hill et al 2008;Bastiani et al 2009;Hansen et al 2009;McMahon et al 2009). PTRF/ cavin-1 is essential for the formation of caveolae (Hill et al 2008;Liu et al 2008) and, like caveolin, has been shown to be associated with LD function and lipid storage in cultured adipocytes (Aboulaich et al 2006), mice (Liu et al 2008), and human patients (Hayashi et al 2009;Rajab et al 2010). …”
Section: Interactions With Caveolae Caveolins and Cavinsmentioning
confidence: 99%